Multimedia-Based Visual Analysis As a Promotional Media At Raharja Internet Cafe (RIC) - Febriyanto, Erick; Aini, Qurotul; afitri, afni (APTISI Transactions on Management (ATM), 2020)
The development of visual communication media is currently widely used as a means of promotion and information technology. By following the development of information technology today, the delivery of information is no longer presented in the conventional form, but now it has been widely applied in electronic form. One of the results of the development of information technology that can be used as a medium for delivering interesting information can be in the form of Graphic Design such as Online Posters and images uploaded on social media. Raharja Internet Cafe or often called RIC is one of the facilities located at Raharja University. Providing all personal needs Raharja in carrying out lecture activities such as Print, Scan, install iPad, also provides accessories for technological devices such as computers and iPads, besides that RIC also serves computer and iPad services. However, RIC still has problems in presenting information relevant to existing developments. Millennials today tend to get and search for information by accessing social media compared to accessing a website. This is one of the important things that must be applied to Raharja Internet Cafe in conducting socialization and marketing. Therefore, the author was given the opportunity to be able to do the Job Training Lecture (KKP) on Raharja Internet Cafe to apply the knowledge gained in the lecture curriculum. Then the author also gained a lot of knowledge about the world of work that had not previously been obtained in the lecture process. Which in the end, each task and the work that has been done by the author while carrying out the Job Training Lecture (KKP), will be summarized in the Job Training Lecture report.